Percutaneous closure of the left atrial appendage in patients with diabetes mellitus. (September 2017) - Azizy, Obayda; Rammos, Christos; Lehmann, Nils; Rassaf, Tienush; Kälsch, Hagen
Background: Left atrial appendage closure is a preventive treatment of atrial fibrillation–related thrombo-embolism. Patients with diabetes mellitus have increased risk for a negative outcome in percutaneous cardiac interventions. We assessed whether percutaneous left atrial appendage closure is safe and effective in patients with diabetes mellitus. Methods: We included 78 patients (mean age of 74.4 ± 8.3 years) with indication for left atrial appendage closure in an open-label observational single-centre study. Results: Patients with diabetes mellitus ( n = 31) were at higher thrombo-embolic and bleeding risk (CHA2 DS2 -VASc: 4.5 ± 0.9, HAS-BLED: 4.7 ± 0.7) compared to patients without diabetes mellitus ( n = 47, CHA2 DS2 -VASc: 3.5 ± 1.0, HAS-BLED: 4.1 ± 0.8; p < 0.001 for both). Pre- and periprocedural risk was elevated in patients with diabetes mellitus (Euro II-Score: 6.6 ± 3.7 vs 3.9 ± 1.9, p < 0.01; Society of Thoracic Surgeons (STS)-Score: 4.0 ± 2.5 vs 2.6 ± 1.2, p < 0.01). Procedural success was similar. Periprocedural major adverse cardiac and cerebrovascular events occurred in one patient from the control group (2.1%), whereas patients with diabetes mellitus had no events ( p = 0.672). Follow-up of 6 months revealed no bleeding complication in both groups. No stroke occurred in follow-up, and left atrial appendage flow velocity reduction (55.6 ± 38.6 vs 51.4 ± 19.1 cm/s, p = 0.474) and rate of postinterventional leakage in the left atrial appendage were comparable (0% vs 2.1%, p = 0.672). Conclusion: Despite patients with diabetes mellitus are high-risk patients, the outcome of percutaneous left atrial appendage closure is similar to patients without diabetes mellitus.